The ethics of patient - provider relationships : proceedings and abstracts and papers : East-West Bioethic Conference III : Prague, 1991 (SIGNA Brno, 1991)
A collection of abstracts of papers presented at a conference that focused on clinical ethics and patient-provider relationships. Intended for professional public.
Keywords: Patient Care; Professional-Patient Relations; Ethics, Clinical; klinická etika; etika, bioetika, lékařská etika; Paternalism; vztahy mezi zdravotnickým pracovníkem a pacientem; paternalismus; péče o pacienta